2018
DOI: 10.7554/elife.42209
|View full text |Cite
|
Sign up to set email alerts
|

Screening for insulin-independent pathways that modulate glucose homeostasis identifies androgen receptor antagonists

Abstract: Pathways modulating glucose homeostasis independently of insulin would open new avenues to combat insulin resistance and diabetes. Here, we report the establishment, characterization, and use of a vertebrate ‘insulin-free’ model to identify insulin-independent modulators of glucose metabolism. insulin knockout zebrafish recapitulate core characteristics of diabetes and survive only up to larval stages. Utilizing a highly efficient endoderm transplant technique, we generated viable chimeric adults that provide … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 80 publications
0
10
0
Order By: Relevance
“…In humans and mammals, insulin is the only pancreatic cell hormone known to directly regulate blood glucose. 46–49 Mullapudi et al 50 has confirmed that insulin in zebrafish is also as important as in humans and mammals. Prior studies have demonstrated that the development of zebrafish cell is highly conserved with that of mammals.…”
Section: Discussionmentioning
confidence: 97%
“…In humans and mammals, insulin is the only pancreatic cell hormone known to directly regulate blood glucose. 46–49 Mullapudi et al 50 has confirmed that insulin in zebrafish is also as important as in humans and mammals. Prior studies have demonstrated that the development of zebrafish cell is highly conserved with that of mammals.…”
Section: Discussionmentioning
confidence: 97%
“…Embryos were staged by hpf at 28.5°C (Kimmel et al, 1995). The following lines were used: Tg(fabp10a: EGFP) as3 (Her, Yeh, and Wu, 2003), Tg(ins:Kaede) jh6 (Pisharath et al, 2007), Tg(ins:dsRed) m1018 (Shin et al, 2008), Tg(ins:Hsa.HIST1H2BJ-GFP;ins:DsRed) s960 (Ninov et al, 2013) abbreviated Tg(ins:H2B-GFP;ins: DsRed), Tg( pck1:Luciferase) s952 (Gut et al, 2013), Tg BAC (neuroD: EGFP) nl1 (Obholzer et al, 2008), pdx1 sa280 (Kimmel et al, 2015), insulin bns102 (Mullapudi et al, 2018), Tg(insulin:loxP:mCherrySTOP: loxP:H2B-GFP; cryaa:Cerulean) s934 (Hesselson et al, 2011), Tg(sox17: GFP) s870 (Sakaguchi et al, 2006), Tg(Tp1bglob:H2BmCherry) S939 (Ninov et al, 2012), Tg(ubb:loxP:CFP:loxP:H2B-mCherry) jh63 (Wang et al, 2015), Tg BAC (arxa:Cre) bns250 (this study), Tg BAC ( pdx1:EGFP) bns13 (this study), Tg BAC ( pdx1:luciferase2) bns17 (this study) and Tg(ins:loxP-Eco.NfsB-mCherry-loxP-luciferase) bns152 abbreviated as Tg(ins:mCherry) (this study).…”
Section: Zebrafish Husbandry and Strainsmentioning
confidence: 99%
“…The development of new imaging technologies, such as light sheet microscopy, new fluorophores and biosensors, will allow even more detailed images to be acquired over longer periods of time without bleaching or photo toxicity. Technologies such as small molecule screens [ 151 , 152 , 153 ] and protein-protein interaction assays (e.g., BioID) [ 154 , 155 ] are extending the toolbox for using the zebrafish model. The emergence of single cell sequencing technologies within the last years enabled the dissection of the developmental trajectories of cells and their heterogeneity within one cell lineage [ 156 ].…”
Section: Perspectivementioning
confidence: 99%